CLINICAL AND PATHOGENETIC EFFECTIVENESS OF VARIOUS PHARMACOTHERAPEUTIC MODES IN SEVERE BRONCHIAL ASTHMA IN CHILDREN - L.M. Ogorodova; I.A. Deev; I.I. Ivanchuk (Педиатрическая фармакология)
Open prospective randomized study in parallel groups was carried out to evaluate clinical (the amount of children who reached the control level by goal) and pathogenetic (the influence on the dynamics of the antiapoptotic eosinophil effectors expression) effectiveness of various pharma cotherapeutic modes in severe children's asthma. All patients (n = 60) underwent the evaluation of the expression of mRNA IL 5, bcl 2, bcl Xl against the backgrounds of the application of three modes of therapy (monotherapy by fluticasone propionate, combination of fluticasone propionate with sustained release theophyllines and fluticasone propionate with salmeterol). It has been found that usage of pharmacotherapeutic mode of fluticasone propionate with salmeterol by the end of the first month of treatment brings about the increase in the apoptotic activity of eosinophils, and by the end of the treatment period (24 weeks) — this criterion didn't differ from the control values. The usage of the combination of fluticasone propionate and salmeterol is the optimal pharmacotherapeutic mode for the treatment of severe asthmain children, as it ensures the achievement of the control over symptoms and is the most effective in the aspect of eosinophil apoptosis regulation, therefore results in slackening of inflammatory activity of the respiratory tract.Key words: severe bronchial asthma, children, eosinophils, apoptosis, IL 5, bcl 2, bcl-Xl, fluticasone propionate, salmeterol, sustaine-release theophyllines, treatment.